Describing Picture Technique in Improving Students' Speaking Skill at the Second Grade of SMP Swasta Taruna Karya Kupang in the school year 2023/2024: English - Fanggidae, Yennsy Mervilen; Isu, Rudolof (Universitas Persatuan Guru 1945 NTT, 2024)
This study entitled